Crustal anisotropy in a subduction zone forearc: Northern Cascadia. Issue 9 (9th September 2014) - Matharu, G.; Bostock, M. G.; Christensen, N. I.; Tromp, Jeroen
Abstract S‐wave splitting analyses using low‐frequency earthquake templates at three‐component stations across southern Vancouver Island and northern Washington indicate the presence of a heterogeneous distribution of crustal anisotropy in the North American plate. For southern Vancouver Island, we investigate contributions to anisotropy from the Leech River Complex, a terrane composed of strongly foliated phyllites and schists with steeply dipping foliations striking east‐west. Fast directions across mainland southern Vancouver Island are subparallel to the dominant Leech River Complex foliation direction. East‐to‐west increases in delay times and small‐scale azimuthal variations in fast directions indicate heterogeneous anisotropy. We test azimuthally anisotropic Leech River Complex models constrained by previous geological and seismic reflection studies, through forward modeling using 3‐D spectral element method simulations. The preferred model of a north/northeast shallowly dipping wedge of Leech River Complex material with varying orientation of anisotropy terminating at midcrustal levels explains the splitting observations at a majority of southern Vancouver Island stations. For stations where anisotropic Leech River Complex models do not recreate observations, fast directions are subparallel to local estimates of maximum compressive horizontal stress, suggesting that fluid‐filled cracks could be a source of anisotropy. We assert that the Leech River Complex is the primary source of crustal anisotropy beneath southern Vancouver Island, not cracks as suggested by prior studies. Fast directions at stations on northern Washington exhibit variations with azimuth and incidence angle suggesting complex anisotropy interpreted as due to a combination of cracks and preferred mineral orientation of metamorphosed slates of the Olympic core rocks. These slates may also underlay stations on southern Vancouver Island and represent another source of anisotropy.